2010
DOI: 10.1787/5km4pskmkr27-en
|View full text |Cite
|
Sign up to set email alerts
|

Markets in Education

Abstract: JT03290846 OECD DIRECTORATE FOR EDUCATION OECD Education Working Paper SeriesThis series is designed to make available to a wider readership selected studies drawing on the work of the OECD Directorate for Education. Authorship is usually collective, but principal writers are named. The papers are generally available only in their original language (English or French) with a short summary available in the other.Comment on the series is welcome, and should be sent to either edu.contact@oecd.org or the Directora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 170 publications
(218 reference statements)
0
15
0
Order By: Relevance
“…I do not discuss the specific data results of these mostly quantitative-based studies (for this debate see Dupriez & Dumay, 2011;Waslander, et al 2010), yet I raise conceptual and empirical arguments from a different angle.…”
Section: Final Thoughtsmentioning
confidence: 98%
See 1 more Smart Citation
“…I do not discuss the specific data results of these mostly quantitative-based studies (for this debate see Dupriez & Dumay, 2011;Waslander, et al 2010), yet I raise conceptual and empirical arguments from a different angle.…”
Section: Final Thoughtsmentioning
confidence: 98%
“…The aim is not to offer a comprehensive review, hoping to assess the benefits/disadvantages of these policies. In effect, there are available reviews on the impact of market-oriented policies (Waslander, Pater, & van der Weide, 2010) and accountability policies (Anstorp, 2010). This paper focuses particularly on critical policy literature (56 papers and 12 books).…”
Section: Introductionmentioning
confidence: 99%
“…For example, on information access, Alegre and Benito (2012) reveal that parents in advantaged socioeconomic positions are better able to access privileged information (i.e., insider information on a school through social networks) than marginalized families, who must rely on "under-capitalized channels" (i.e., publically-available information). This information asymmetry influences the choice sets that parents construct when exploring options for their children (Waslander, Pater, & van der Weide, 2010). It can also lead to greater segregation of students along socio-economic or racial characteristics (Reay, 2004).…”
Section: Theory Vs Reality In the Literaturementioning
confidence: 99%
“…Yet other studies have suggested that the perception of competition depends on the purpose of charter schools, for example, and the context into which they are introduced. Not surprisingly, TPSs may not perceive charter schools as a threat if the latter are intended to serve marginalized or low-performing students and if the TPSs experience no negative financial impact as a result of the charter schools (Waslander, Pater, & van der Weide, 2010).…”
Section: Theory Vs Reality In the Literaturementioning
confidence: 99%
“…The impact of school performance indicators on parents seems to be small because parents' choices are only partly based on rational decision making. Social, cultural, and pragmatic factors play an important role as well (Waslander, Pater, & van der Weide, 2010).…”
Section: The Use Of Open Performance Data: Toward a Conceptual Modelmentioning
confidence: 99%